PENGARUH FASAD KACA DENGAN MATERIAL PCM TERHADAP SUHU INDOOR PADA HIGH RISE APARTMENT - Litani Evitasari; Ima Defiana; FX Teddy Badai Samodra (Jurnal Arsitektur ARCADE, 2023)
In recent years, the selection of building envelope designs frequently using fabricated materials. Glass is commonly chosen because it can make the façade of building more aesthetic and also it’s installation is quite fast. On the other hand, glass is a good conductor, so the heat from outside can be transferred directly into the building, causing the increase of indoor temperature. This research try to compare combinations of glass materials and various types of PCM that can decrease indoor temperature on the high rise apartment at Surabaya, Indonesia. The purpose of this research is to propose the impact of the application of PCM material to the apartment's glass facade on the indoor temperature of the building based on thermal properties and window-to-wall ratio (WWR). This research using experiment method with the assistance of DesignBuilder software. This research showed that the value of conductivity and density have the most significant effects on decrease indoor temperature. Adding Bio-PCM to the glass facade can reduce the temperature by 2 to 4 K. Beside that, the most significant temperature decrease at 80% WWR simulation in the coldest month with the building facing east. The temperature decreased by 1.3 K. The difference in temperature that occurs in the western orientation in hottest and coldest month reaches 0.57 K.